Circular RNAs—The Road Less Traveled - Guria, Ashirbad; Sharma, Priyanka; Natesan, Sankar; Pandi, Gopal (Frontiers in Molecular Biosciences, 2020)
Circular RNAs are the recent addition in the non-coding RNA family which has started gaining recognition after a decade of its non-existence. However, the first few reports in the beginning of this decade and the accumulating evidences thereafter has evoked the RNA researchers to navigate further in the quest for exploration of circular RNAs. Joining of 5’ and 3’ ends of RNA molecules by backsplicing forms circular RNAs during co-transcriptional or post-transcriptional processes. These molecules are capable of effectively sponging microRNAs, thereby regulates the cellular processess, as evidenced from numerous animal and plant systems. Preliminary studies have shown that circular RNAs have imperative role in transcriptional regulation, protein translation, and its possible therapeutic potential. High stability of circular RNA is rendered by its closed ends; nevertheless they are prone to degradation by circulating endonucleases in serum or exosomes or by microRNA-mediated cleavage due to its high complementarity. However, identification of circular RNAs using diverse methodologies and delineating its possible role and mechanism in the regulation of cellular and molecular architecture have given a new direction to the circular RNA research. In this current review, we have discussed the possible mechanism of circular RNA biogenesis, its structure, properties, degradation, and the growing evidences in the detection methods and its role in animal and plant system.